1984
DOI: 10.1073/pnas.81.13.3939
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and structure determination of cDNA for cutinase, an enzyme involved in fungal penetration of plants

Abstract: The primary structure of cutinase, an extracellular fungal enzyme involved in the penetration of plants by pathogenic fungi, has been determined from the nucleotide sequence of cloned cDNA. Clones containing cDNA made from poly(A)+ RNA isolated from fungal cultures induced to synthesize cutinase were screened for their ability to hybridize with the [32P]cDNA for mRNA unique to the induced culture. The 75 cDNA clones thus identified were screened for the cutinase genetic code by hybrid-selected translation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 29 publications
(18 reference statements)
1
36
0
Order By: Relevance
“…Amino acid sequence of some peptides obtained from one of these enzymes (cutinase 1) matched with that predicted from the cDNA of the induced cutinase transcript (10). The present results reveal the occurrence of other cutinase genes that could encode enzymes that are similar but not identical to cutinase 1.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Amino acid sequence of some peptides obtained from one of these enzymes (cutinase 1) matched with that predicted from the cDNA of the induced cutinase transcript (10). The present results reveal the occurrence of other cutinase genes that could encode enzymes that are similar but not identical to cutinase 1.…”
Section: Discussionmentioning
confidence: 62%
“…Samples of each cutinase were reduced, and SH groups were derivatized with 14 C-labeled iodoacetamide (2.8 Ci/mol, PerkinElmer Life Sciences) and digested with trypsin as described before (10). The digests were fractionated by high pressure liquid chromatography on a Nova-PacC 18 Radial-Pac column (Waters Associates) with a linear gradient of 5-65% acetonitrile in water containing 0.1% trifluoroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the liberated fragments are able to induce de novo synthesis of cutinase (Wolosbuk & Kolattukudy, 1986). The gene encoding cutinase of F. solani has been cloned (Soliday et al, 1984), and it has been shown that plant cutin monomers, together with a protein factor of approximately 100 kDa, are necessary to initiate transcription of the cutinase gene in isolated nuclei (Podila, Dickman & Kolattukudy, 1988). Insertion of the cutinase gene from E. solani into the genome of a wound pathogen of papaya fruits, the ascomycete Mycosphaerella sp., enabled this fungus to infect papaya fruits through the intact cuticle (Dickman, Podila & Kolattukudy, 1989).…”
Section: Production Of Cuticle-and Cell Wall-degrading Enzymes By Hyphaementioning
confidence: 99%